Analysis of sound absorption by a three-layer resonant and absorbing structure - WERNEROWSKI, Krzysztof (Archives of Acoustics, 1988)
The paper presents an analogous method of calculating resonance frequencies of a three-layer perforated structure. It was found that a model of vibrations with three degrees of freedom can be applied here. The possibility of widening frequency bands by using absorbing layers was developed and investigated. Effective attenuation of harmful noise with relatively low frequencies was stated.